Biodegradation of Gum tragacanth acrylic acid based hydrogel and its impact on soil fertility. (May 2015) - Saruchi,; Kaith, Balbir Singh; Jindal, Rajeev; Kumar, Vaneet
Abstract: In the present work, biodegradation study of Gum tragacanth -acrylic acid based hydrogel was conducted using soil burial and composting methods. Within 77 days, complete degradation of synthesized hydrogel was observed in the composting method, while 92.29% of degradation was observed in soil burial method. Scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR) techniques gave the evidence and progress of biodegradation at different stages. Impact of biodegradation of hydrogels on soil fertility was studied through macroanalysis of soil before and after biodegradation studies. Plant growth of Phaseolus vulgaris showed that test sample soil was better for plant growth in comparison to the garden soil. Synthesized hydrogel was also evaluated for controlled release of fertilizer. Fertilizer release kinetic through the synthesized matrix showed Non-fickian diffusion behaviour.